Artificial Intelligence and IoT based Smart Irrigation system for Precision Farming - et. al., Dr. Hetal Patel, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The application of the technology needs to be employed to the all phase of agriculture. It needs to be precision agriculture rather than traditional as optimization of the resources give the benefit to the farmers and ultimately affect to the GDP of the country positively. The crop production must be increase as the demand is high and production is low. Here, in this paper, the model and framework are proposed for the irrigation system. The objective is to save the water and supply it to the crop only when it is actually required. The Internet of Things (Iot) with the artificial intelligence technologies are adopted to control the irrigation system using smart phone. The moisture level of soil is detected and stored using various sensors which are spread over the farm. The aim is to automate the irrigation system for the crop